Does Artificial Intelligence Go beyond the Limits of Religious Authority? An Ethical Review on IslamGPT - Mohammad Fattahun Niam (Al'Adalah, 2024)
The rapid advancements in artificial intelligence (AI) have begun challenging the traditional boundaries of religious authority, historically upheld by scholars and clerics. This study examines IslamGPT, an AI platform designed to provide answers on Islamic teachings, and explores its ethical implications within the context of religious authority. While AI, like IslamGPT, offers convenience in accessing religious knowledge, it raises concerns about accuracy, credibility, and the potential erosion of established religious guidance. This article analyzes the ethical dimensions of utilizing AI for religious purposes, emphasizing the need for guidelines to navigate this emerging landscape. The study finds that reliance on AI for religious advice may blur the lines of legitimate authority, highlighting the necessity of direct verification with religious experts to maintain doctrinal integrity. The paper concludes that while AI can support religious education, its use in delivering authoritative religious decisions must be approached with caution, incorporating human oversight to preserve the sanctity of religious teachings.